2013
DOI: 10.1038/eye.2013.248
|View full text |Cite
|
Sign up to set email alerts
|

Optimising biometry for best outcomes in cataract surgery

Abstract: Biometry has become one of the most important steps in modern cataract surgery and, according to the Royal College of Ophthalmologists Cataract Surgery Guidelines, what matters most is achieving excellent results. This paper is aimed at the NHS cataract surgeon and intends to be a critical review of the recent literature on biometry for cataract surgery, summarising the evidence for current best practice standards and available practical strategies for improving outcomes for patients. With modern optical biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…The ARE was within AE0.25, AE0.50 and AE1.00 D in 32%, 55% and 83% of the cases in this study after 12 months. In comparison, in cataract surgery, the ARE is within AE0.25,AE0.50 and AE1.00 D in 19%, 55-71% and 85-96%(Eleftheriadis 2003; Gale et al 2009;Aristodemou et al 2011;Sheard 2014). The RE outcomes of combined surgery and cataract surgery in vitrectomized eyes are thus comparable to cataract surgery alone, and the vitreoretinal procedure seems not to have an influence on the refractive outcome in the long term (12 months).…”
Section: Paper IImentioning
confidence: 96%
“…The ARE was within AE0.25, AE0.50 and AE1.00 D in 32%, 55% and 83% of the cases in this study after 12 months. In comparison, in cataract surgery, the ARE is within AE0.25,AE0.50 and AE1.00 D in 19%, 55-71% and 85-96%(Eleftheriadis 2003; Gale et al 2009;Aristodemou et al 2011;Sheard 2014). The RE outcomes of combined surgery and cataract surgery in vitrectomized eyes are thus comparable to cataract surgery alone, and the vitreoretinal procedure seems not to have an influence on the refractive outcome in the long term (12 months).…”
Section: Paper IImentioning
confidence: 96%
“…; Aristodemou et al. 2011; Sheard ). The RE outcomes of combined surgery and cataract surgery in vitrectomized eyes are thus comparable to cataract surgery alone, and the vitreoretinal procedure seems not to have an influence on the refractive outcome in the long term (12 months).…”
Section: Discussionmentioning
confidence: 99%
“…found that 80% of cases in a large database could achieve refraction within ±0.5 D of target albeit this cohort consisted of highly experienced surgeons only and excluded comorbidity factors . Considering the combination of modern optical biometry, informed formula choice and IOL constant optimization, Sheard more recently proposed that surgeons should be able to achieve 60% and 90% within ±0.5 and ±1.0 D, respectively …”
Section: Discussionmentioning
confidence: 99%